Risk factors for post caesarean surgical site infection at a tertiary care center in Eastern Nepal - Chhetry, Manisha; Subedi, Shanti; Banerjee, Basudeb (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Post cesarean surgical site infection (SSI) is one of the commonly encountered complications which considerably increase the burden to health care. It is caused due to the interplay of various patient related, procedure related and iatrogenic factors. This study aims at identifying common risk factors for post cesarean SSI at our centre. Materials & Methods: This was a prospective observational study conducted from July 2015 to December 2015, in which all patients who were admitted with post cesarean SSI or developed SSI during their stay were included and their risk factors were studied. Results: Emergency procedures (82.97%) were more likely to develop SSI as compared to elective cesarean (17%). Among the patient related risk factors most of them were nulliparous (48.9%), term gestation (42.6%), malnourished (53.1%) and had history of prolonged leaking (44.68%) The mean age was 24.04±4.6years.Most of the patients who developed SSI were operated for repeat cesarean and fetal indications. Most patients who had SSI had at three to five per vaginal examinations (2.72±2). 66% of patient who had SSI had duration of surgery more than one hour. 68% of the surgeries which developed SSI were done by residents as compared to 32% of those done by consultants Conclusion: The commonly associated risk factors linked with post cesarean SSI are maternal age, emergency procedures, prolonged membrane rupture, multiple vaginal examinations, malnutrition and the experience of surgeon.